All-Around Trade Liberalization and Firm-Level Employment: Theory and Evidence from China - Antonio Rodriguez-Lopez; Miaojie Yu (Center for Economic Studies and ifo Institute (CESifo), 2017)
Chinese firms faced an all-around trade liberalization process during the early 2000s: lower barriers from other countries on Chinese goods, and lower Chinese barriers on other countries' goods and inputs. Using novel firm-level tariff data for trading Chinese manufacturing firms, this paper disentangles the effects of each type of trade liberalization on Chinese firm-level em-ployment. For each firm type, reductions in Chinese and foreign final-good tariffs are associated with job destruction in low-productivity firms and job creation in high-productivity firms. In contrast, the net effect of reductions in Chinese input tariffs is limited to job destruction in low-productivity ordinary exporters.
Keywords: F12; F14; F16; 330; firm-level employment; firm-level tariffs; heterogeneous firms